2002
DOI: 10.1042/bj20011678
|View full text |Cite
|
Sign up to set email alerts
|

Fuc(α1→3)GalNAc-: the major antigenic motif of Schistosoma mansoni glycolipids implicated in infection sera and keyhole-limpet haemocyanin cross-reactivity

Abstract: The aim of the present study was the characterization of the dominant epitope present on Schistosoma mansoni glycolipids, which causes cross-reactivity of S. mansoni and S. haematobium infection sera with keyhole-limpet haemocyanin (KLH). To this end, the monoclonal antibody M2D3H was chosen for its similar behaviour in high-performance TLC immunostaining and inhibition-ELISA to infection sera. Individual, structurally defined oligosaccharides derived from S. mansoni egg glycolipids were tested for their bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
48
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 27 publications
12
48
0
Order By: Relevance
“…1). In contrast to rabbit hyperimmune serum raised against KLH, antibody binding was mostly eliminated by mild HF treatment, which results in a release of fucose residues leaving the remaining carbohydrate chains largely intact (23). In agreement with previous data (22) it may be, therefore, concluded that cross-reacting oligosaccharides comprise a fucosylated carbohydrate epitope.…”
Section: Isolation Of Klh Oligosaccharides Sharing Carbohydrate Epitosupporting
confidence: 78%
“…1). In contrast to rabbit hyperimmune serum raised against KLH, antibody binding was mostly eliminated by mild HF treatment, which results in a release of fucose residues leaving the remaining carbohydrate chains largely intact (23). In agreement with previous data (22) it may be, therefore, concluded that cross-reacting oligosaccharides comprise a fucosylated carbohydrate epitope.…”
Section: Isolation Of Klh Oligosaccharides Sharing Carbohydrate Epitosupporting
confidence: 78%
“…Given the robust expression via immunostaining in schistosomula and adults (Fig. 6B), it is possible that the glycan epitope also is expressed on glycolipids, which is consistent with previous reports of lipid antigens (13,(63)(64)(65)(66).…”
Section: Preparation Of N-glycans From Schistosoma Mansoni Eggssupporting
confidence: 78%
“…Although the nature of the oligosaccharides on the surface of KLH has not been completely elucidated, those identified to date have been shown to contain unique oligosaccharide patterns, resulting in novel structures (45,46). These novel structures, together with the high levels of cross-reactivity with a variety of carbohydrate Ags, may contribute to the immunogenicity of KLH (47).…”
Section: Discussionmentioning
confidence: 99%
“…The cross-reactive epitope was identified (49), and clinical trials with Immucothel, a KLH subunit, are reported (50). In addition, a fucose epitope on the surface of S. mansoni has been found to be cross-reactive with KLH (46,51). Immobilized KLH or anti-KLH Abs have been used to diagnose acute vs chronic infections of S. mansoni (52).…”
Section: Discussionmentioning
confidence: 99%